Advances in bio-logging techniques and their application to study navigation in wild seabirds. (16th February 2019) - Yoda, Ken
ABSTRACT: This review summarizes the advances in bio-logging technology that enables us to monitor foraging behavior, movement, behavioral performance, physiological performance, and sociality in a wide range of bird species, as well as their habitat. Subsequently, navigation is discussed, using long-distance movements in streaked shearwaters as a case study. Moreover, challenges and future research directions in bio-logging science are presented, with focus on: multimodal recording, big data analysis, feedback logging, low-power consumption and power generation systems, logger effects, and capture–recapture methods. GRAPHICAL ABSTRACT: